Efficacy of alum for treatment of recurrent aphthous stomatitis - Nasrin Rafieian; Hamidreza Abdolsamadi; Aliakbar Moghadamnia; Mina Jazayeri; Mohammadali Seif-Rabiee; Mina Salmanzadeh; Shahrbanoo Radi (Babol University of Medical Sciences, 2016)
Background: Recurrent aphthous stomatitis (RAS) is the most common painful ulcers of oral mucosal which can cause many sufferings. Treatment of RAS often includes administration of corticosteroids, analgesics and regulators of the immune system. However, considering the side effects of these medications, even their topical application must be done with caution. Alum is used in traditional medicine for treatment of oral ulcers without significant side effect. This study sought to assess the effect of topical application of alum on aphthous ulcers. Methods: This clinical randomized double-blind placebo-controlled study was conducted on 50 females aged 21 to 27 years. Mucosal adhesive patches were prepared in two forms of basic and 7% alum-containing patches. Subjects in two groups of case and control randomly received the mucosal adhesive patches containing alum and the basic patches, respectively three times in five days. Duration of recovery, changes in size of lesion and severity of pain were recorded. Data were entered into SPSS Version 16 and analyzed using t-test. Results: The average period of full recovery was  7.52 days in the case and 12.2 days in the control groups; which was significantly different (p<0.001). Size of wound and severity of pain were significantly lower at one, three and five days posttreatment compared to baseline values before treatment in the case group (p<0.001) and the difference in this regard between the case and control groups was statistically significant. Conclusion: Alum can significantly decrease the size of aphthous lesions, severity of pain and expedite the recovery of patients with RAS.